Method for manufacturing electrode active material layer and method for manufacturing battery

By applying a slurry on a collector foil and drying at controlled evaporation speeds, the method addresses cracking issues in electrode active material layers, resulting in a stable and high-capacity structure for lithium-ion batteries.

JP2025016022AActive Publication Date: 2025-01-31TOYOTA JIDOSHA KK
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023119021
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-21
Publication Date
2025-01-31
Estimated Expiration
2043-07-21

AI Technical Summary

Technical Problem

Existing methods for manufacturing electrode active material layers in lithium-ion batteries are prone to cracking due to the aggregation of components during the drying process, which is exacerbated by the high capacity requirements for batteries used in electric vehicles.

Method used

A method involving the application of a slurry containing electrode active material and solvent on a collector foil, followed by drying at controlled evaporation speeds defined by specific formulas to minimize cracking, using hot air or laser drying, and maintaining a certain gap between components to allow solvent vaporization without boiling.

Benefits of technology

The method effectively reduces cracking in the electrode active material layer, ensuring a stable and high-capacity electrode structure suitable for electric vehicles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025016022000001_ABST
    Figure 2025016022000001_ABST
Patent Text Reader

Abstract

To provide a method for manufacturing an electrode active material layer in which cracking caused by drying is less likely to occur, and a method for manufacturing a battery including such an electrode active material layer.SOLUTION: A method for manufacturing an electrode active material layer includes coating a current collector foil with a slurry containing an electrode active material and a solvent, and drying the slurry while transporting the slurry-coated current collector foil, thereby obtaining the electrode active material layer. According to the method, in the drying step, drying is performed at an evaporation rate that satisfies the following relational expressions (1) and (2). Relational expression (1) defines evaporation rate of the solvent (mg / cm2sec)≤-2.46×tap density (g / cc) of the electrode active material+5.04, and relational expression (2) defines evaporation rate of the solvent (mg / cm2sec)≤1.20.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for producing an electrode active material layer and a method for producing a battery. [Background technology]

[0002] The electrode active material layer of a lithium-ion battery can be produced by applying an electrode mixture slurry containing an electrode active material and a binder resin, etc., onto a current collector foil and drying it. There is a demand for high-capacity lithium-ion batteries so that they can be used in battery electric vehicles (BEVs) and plug-in hybrid vehicles (PHEVs). In order to achieve high capacity, thickening the electrode active material layer has been considered.

[0003] For example, Patent Document 1 discloses a method for producing an electrode, in which a slurry for forming an electrode composite layer is applied onto a web-shaped current collecting foil, and then the current collecting foil coated with the slurry is transported in one direction in a drying furnace while applying hot air to the coating film to dry the coating film. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2013-084383 A Summary of the Invention [Problem to be solved by the invention]

[0005] When a slurry containing an electrode active material is thickly applied onto a current collector foil and then dried in order to produce a thick electrode active material layer, cracks are likely to occur in the electrode active material layer after drying.

[0006] An object of the present disclosure is to provide a method for producing an electrode active material layer that is less susceptible to cracking due to drying, and a method for producing a battery including such an electrode active material layer. [Means for solving the problem]

[0007] The present inventors have found that the above problems can be solved by the following means. <Aspect 1> Coating a current collector foil with a slurry containing an electrode active material and a solvent; and The slurry is dried while transporting the current collector foil to which the slurry is applied, to obtain an electrode active material layer. Including, In the drying step, drying is performed at an evaporation rate that satisfies the following relational formula (1) and the following relational formula (2): Manufacturing method of electrode active material layer: Relationship (1): Evaporation rate of the solvent (mg / cm 2 ·sec)≦-2.46 × tap density of the electrode active material (g / cc) + 5.04 Relationship (2): The evaporation rate of the solvent (mg / cm 2 sec)≦1.20. <Aspect 2> 2. The method of claim 1, wherein the electrode active material has a tap density of greater than or equal to 1.60 g / cc and less than or equal to 2.00 g / cc. <Aspect 3> 3. The method of claim 1 or 2, wherein the heat source in the drying step is hot air or a laser. <Aspect 4> The method according to any one of aspects 1 to 3, wherein the electrode active material layer has a thickness of 150 μm or more. <Aspect 5> Producing an electrode active material layer by the method according to any one of aspects 1 to 4; How batteries are manufactured. Effect of the Invention

[0008] According to the present disclosure, it is possible to provide a method for producing an electrode active material layer that is less susceptible to cracking due to drying, and a method for producing a battery including such an electrode active material layer. [Brief description of the drawings]

[0009] [Figure 1]FIG. 1 is a graph showing the relationship between the tap density of the electrode active material and the evaporation rate of the solvent, based on the data of Examples 2 to 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, embodiments of the present disclosure will be described in detail. Note that the present disclosure is not limited to the following embodiments, and various modifications can be made within the scope of the present disclosure.

[0011] <<Method for producing electrode active material layer>> The method of the present disclosure for producing an electrode active material layer includes applying a slurry containing an electrode active material and a solvent to a current collector foil, and drying the slurry while transporting the current collector foil to obtain an electrode active material layer. In addition, in the drying step, the method of the present disclosure performs drying at an evaporation rate that satisfies the following relational expressions (1) and (2): Relationship (1): Evaporation rate of the solvent (mg / cm 2 ·sec)≦-2.46 × tap density of the electrode active material (g / cc) + 5.04 Relationship (2): The evaporation rate of the solvent (mg / cm 2 sec)≦1.20

[0012] The present inventors considered that one of the causes of cracking of the electrode active material layer due to drying is the aggregation of components in the coating film caused by the progress of drying of the slurry containing the electrode active material. Specifically, without intending to be bound by any theory, this is presumed as follows. That is, as the drying of the coating film progresses, the components in the coating film aggregate. Therefore, the remaining solvent evaporates from the gaps between the aggregated components, which is likely to cause bumping, and as a result, it is thought that the electrode active material layer is likely to crack.

[0013] In response to this, the present inventors have found that the electrode active material layer is less likely to crack due to drying when the coating film is dried under conditions where the tap density of the electrode active material and the solvent evaporation rate of the slurry satisfy a specific relationship. Specifically, without intending to be bound by any theory, it is believed that by drying the coating film under conditions where the relationship between the tap density of the electrode active material and the solvent evaporation rate of the slurry satisfies a specific relationship, certain gaps are more likely to be generated between the components in the coating film even as the drying proceeds, and the solvent is efficiently evaporated from the gaps, making it possible to prevent bumping, and as a result, it is believed that the electrode active material layer is less likely to crack due to drying of the coating film.

[0014] <Slurry coating process> The method of the present disclosure includes applying to a current collector foil a slurry including an electrode active material and a solvent.

[0015] The current collector foil is not particularly limited as long as it can be used as a current collector foil for a battery. For example, when forming a lithium ion battery, aluminum foil, copper foil, etc. can be used.

[0016] The electrode active material is not particularly limited as long as it can be used as an electrode active material of a battery. Therefore, the electrode active material may be either a positive electrode active material or a negative electrode active material. Among known active materials, two materials having different potentials (charge / discharge potentials) at which a specific ion is absorbed and released can be selected, and the material showing a more noble potential can be used as a positive electrode active material, and the material showing a less noble potential can be used as a negative electrode active material.

[0017] As the positive electrode active material, a known active material may be used. For example, in the case of constructing a lithium ion battery, the positive electrode active material may be lithium cobalt oxide, lithium nickel oxide, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 Various lithium-containing composite oxides such as O2, lithium manganate, and spinel-based lithium compounds can be used. In addition, lithium iron phosphate (LFP) can be used as an olivine-type positive electrode active material. The positive electrode active material may be, for example, particulate, and the size of the particulate is not particularly limited.

[0018] As the negative electrode active material, a known active material may be used. For example, in the case of constructing a lithium ion battery, the negative electrode active material may be a silicon-based active material such as silicon, a silicon alloy, or silicon oxide; a carbon-based active material such as graphite or hard carbon; various oxide-based active materials such as lithium titanate; metallic lithium, a lithium alloy, or the like. The negative electrode active material may be, for example, particulate, and the size of the particulate is not particularly limited.

[0019] In the context of the present disclosure, the slurry may be an electrode mixture slurry. In the context of the present disclosure, an "electrode mixture slurry" refers to a slurry that includes a dispersion medium in addition to an "electrode mixture" and that can be applied and dried to form an electrode active material layer. In addition, the "electrode mixture" optionally includes a solid electrolyte, a conductive assistant, and a binder in addition to the electrode active material.

[0020] The material of the solid electrolyte is not particularly limited, and any material that can be used as a solid electrolyte for use in lithium ion batteries can be used. For example, the solid electrolyte may be a sulfide solid electrolyte.

[0021] Examples of sulfide solid electrolytes include, but are not limited to, sulfide amorphous solid electrolytes, sulfide crystalline solid electrolytes, and argyrodite-type solid electrolytes. Specific examples of sulfide solid electrolytes include Li2S-P2S5-based (Li7P3S 11 , Li3PS4, Li8P2S9, etc.), Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-LiBr-Li2S-P2S5, Li2S-P2S5-GeS2 (Li 13 GeP3S 16 , Li 10 GeP2S 12 ), LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li 7-x P.S. 6-x Cl x etc.; or combinations thereof, but are not limited to these.

[0022] The sulfide solid electrolyte may be a glass or a crystallized glass (glass ceramic).

[0023] The conductive assistant is not particularly limited. For example, the conductive assistant may be VGCF (Vapor Grown Carbon Fiber), acetylene black (AB), Ketjen Black (KB), carbon nanotube (CNT), carbon nanofiber (CNF), etc., but is not limited thereto.

[0024] The binder is not particularly limited. For example, the binder may be a material such as polyvinylidene fluoride (PVdF), butadiene rubber (BR), or styrene butadiene rubber (SBR), or a combination thereof, but is not limited thereto.

[0025] The solvent is not particularly limited as long as it can disperse the electrode active material and does not significantly impair the properties of the electrode active material when dispersed in the solvent. Examples of the solvent include water and N-methyl-2-pyrrolidone (NMP).

[0026] The method for applying the slurry is not particularly limited, but a blade application method is exemplified.

[0027] <Slurry drying process> The method of the present disclosure includes drying the slurry while transporting the current collector foil to which the slurry is applied, to obtain an electrode active material layer.

[0028] By controlling the drying conditions in the drying step, the solvent evaporation rate can be adjusted.

[0029] In the method of the present disclosure, the heat source in the drying step may be hot air or a laser. When the solvent is water and hot air is used, the drying conditions may be 5 m / s or more, 10 m / s or more, or 15 m / s or more at 90° C., and 40 m / s or less, 35 m / s or less, or 30 m / s or less at 120° C., and 3 m / s or more, 8 m / s or more, or 10 m / s or more, and 30 m / s or less, 25 m / s or less, or 20 m / s or less at 150° C. When the solvent is water and a laser is used, the drying conditions may be an energy density of 0.5 W / cm 2 More than 1.0W / cm 2 More than 1.5W / cm 2 More than 2.0W / cm 2 or more than 2.5W / cm 2 or more, 5.0 W / cm 2 Below, 4.5W / cm 2 Below, 4.0W / cm 2 or less than 3.5W / cm 2 It may be the following:

[0030] An example of a method for transporting the current collector foil is a method using transport rollers.

[0031] In the drying step of the method of the present disclosure, drying is performed at an evaporation rate that satisfies the following relational formula (1) and the following relational formula (2). Relationship (1): Evaporation rate of the solvent (mg / cm 2 sec)≦-2.46 × tap density of electrode active material (g / cc) + 5.04 Relationship (2): Evaporation rate of the solvent (mg / cm 2 sec)≦1.20

[0032] As mentioned above, the method of adjusting the solvent evaporation rate includes controlling the drying conditions. 2 sec greater than 0.10mg / cm 2 ·sec or more, 0.20mg / cm 2·sec or more, 0.30mg / cm 2 sec or more, or 0.40 mg / cm 2 sec or more, and 2 ·sec or less, 0.90mg / cm 2 ·sec or less, 0.80mg / cm 2 ·sec or less, 0.70mg / cm 2 sec or less, or 0.60 mg / cm 2 The solvent evaporation rate can be calculated from the weight change of the solvent evaporation amount using a weighing scale. A personal electronic balance manufactured by A&D Corporation can be used as the weighing scale.

[0033] The tap density of the electrode active material in the method of the present disclosure may be 1.60 g / cc or more and 2.00 g / cc or less. The tap density of the electrode active material may be 1.65 g / cc or more and 1.90 g / cc or less, 1.80 g / cc or less, or 1.75 g / cc or less.

[0034] The tap density of the electrode active material can be measured by a method specified in JIS K1469:2003 using a general tapping type density measuring device, for example, a Tap Denser manufactured by Seishin Enterprise Co., Ltd.

[0035] In the method of the present disclosure, when the slurry contains a component other than the electrode active material, the electrode active material may be the main component in the electrode mixture. This can prevent the solvent in the slurry from being difficult to volatilize due to the components other than the electrode active material in the electrode mixture. Here, in the method of the present disclosure, the "main component" means a component whose mass ratio in the electrode mixture is 50 mass% or more, 60 mass% or more, 70 mass% or more, 80 mass% or more, or 90 mass% or more.

[0036] For example, when the electrode active material is not the main component of the electrode mixture, the value of the electrode mixture may be used as the tap density, which allows the influence of components other than the electrode active material in the electrode mixture on the ease of volatilization of the solvent in the slurry to be taken into consideration.

[0037] The thickness of the electrode active material layer produced by the method of the present disclosure may be 150 μm or more, 200 μm or more, or 250 μm or more, and may be 500 μm or less, 450 μm or less, 400 μm or less, or 350 μm or less. The thickness of the electrode active material layer within the above range is preferable from the viewpoint of increasing the capacity of the electrode active material layer for use in, for example, BEVs and PHEVs.

[0038] <Battery manufacturing method> The disclosed method of manufacturing a battery includes producing an electrode active material layer.

[0039] For the method for producing the electrode active material layer, reference can be made to the above description regarding the method for producing the electrode active material layer of the present disclosure.

[0040] The method of the present disclosure for producing a battery may include, in addition to producing an electrode active material layer, arranging an anode current collector layer, an anode active material layer, an electrolyte layer, a cathode active material layer, and a cathode current collector layer in this order. In this case, the electrode active material layer produced by the method of the present disclosure can be used for either or both of the anode active material layer and the cathode active material layer. EXAMPLES

[0041] <<Preparation of electrode active material layer>> Example 1 Lithium iron phosphate (LFP) with a tap density of 1.70 g / cc was used as the electrode active material. An electrode mixture containing 98 parts by mass of this LFP, 0.4 parts by mass of carboxymethyl cellulose (CMC), and 1.6 parts by mass of styrene butadiene rubber (SBR) was dispersed in water as a solvent to prepare an electrode mixture slurry (solid content rate of the electrode mixture slurry was 75% by mass). This slurry was applied to a current collector foil. While transporting this current collector foil with a transport roller, the slurry was dried by applying hot air at 150°C and 15 m / sec to obtain an electrode active material layer with a thickness of 300 μm. The solvent evaporation rate in the drying process was 0.5 mg / cm 2 -sec.

[0042] Example 2 An electrode active material layer was obtained in the same manner as in Example 1, except that LFP with a tap density of 1.60 g / cc was used as the electrode active material, and the slurry was dried by applying hot air at 120° C. and 10 m / s. The solvent evaporation rate in this drying step was 1.1 mg / cm 2 -sec.

[0043] Example 3 An electrode active material layer was obtained in the same manner as in Example 1, except that LFP with a tap density of 1.75 g / cc was used as the electrode active material. The solvent evaporation rate in this drying step was 0.74 mg / cm 2 -sec.

[0044] Example 4 An electrode active material layer was obtained in the same manner as in Example 1, except that LFP with a tap density of 1.825 g / cc was used as the electrode active material. The solvent evaporation rate in this drying step was 0.54 mg / cm 2 -sec.

[0045] Example 5 An electrode active material layer was obtained in the same manner as in Example 1, except that LFP with a tap density of 1.90 g / cc was used as the electrode active material. The solvent evaporation rate in this drying step was 0.365 mg / cm 2 -sec.

[0046] Comparative Example 1 An electrode active material layer was obtained in the same manner as in Example 1, except that LFP having a tap density of 1.90 g / cc was used as the electrode active material.

[0047] Comparative Example 2 Energy density 3W / cm 2 An electrode active material layer was obtained in the same manner as in Example 1, except that the slurry was dried by irradiating it with a laser of 1.3 g / cm. The solvent evaporation rate in this drying step was 1.3 mg / cm. 2 -sec.

[0048] In each of the above examples, the tap density of the electrode active material was measured using a tapping-type density measuring device (Tap Denser, Seishin Enterprise Co., Ltd.) according to the method specified in JIS K1469: 2003. The evaporation rate of the solvent was calculated from the weight change of the solvent evaporation amount using a weighing scale (A&D personal scale).

[0049] "evaluation" The electrode active material layer produced in each example was visually inspected for the presence or absence of cracks.

[0050] "result" A graph showing the relationship between the tap density and the solvent evaporation rate of the electrode active material based on Examples 2 to 5 is shown in FIG. 1. The linear approximation in this graph corresponds to the relational expression (1) of the present disclosure. No cracks occurred in the electrode active material layers of the Examples produced by the method of the present disclosure, which satisfied the relational expressions (1) and (2). In contrast, cracks occurred in the electrode active material layers of Comparative Examples 1 and 2, which did not satisfy the relational expression (1). Furthermore, bumping of the solvent was observed in the electrode active material layer of Comparative Example 2, in which the solvent evaporation rate did not satisfy the relational expression (2).

Claims

1. Coating a current collector foil with a slurry containing an electrode active material and a solvent; and drying the slurry while transporting the current collector foil on which the slurry is applied to obtain an electrode active material layer; In the drying step, drying is performed at an evaporation rate that satisfies the following relational formula (1) and the following relational formula (2): Manufacturing method of electrode active material layer: Relational formula (1): Evaporation rate of the solvent (mg / cm 2 sec)≦−2.46×tap density of the electrode active material (g / cc)+5.04 Relational formula (2): Evaporation rate of the solvent (mg / cm 2 ・sec)≦1.

20.

2. 2. The method of claim 1, wherein the electrode active material has a tap density of 1.60 g / cc or more and 2.00 g / cc or less.

3. The method according to claim 1 , wherein the heat source in the drying step is hot air or a laser.

4. The method of claim 1 , wherein the electrode active material layer has a thickness of 150 μm or more.

5. Producing an electrode active material layer by the method according to any one of claims 1 to 4; How batteries are manufactured.

Citation Information

Patent Citations

  • Method for prolonging cyclic service life of lithium iron phosphate battery

    CN103956460A

  • Method of manufacturing positive electrode plate for nonaqueous electrolytic liquid secondary battery, and nonaqueous electrolytic liquid secondary battery using positive electrode plate

    JP2009081072A

  • Manufacturing method of cathode plate for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery

    JP2010108624A

  • Lithium iron phosphate composite material, production method and use thereof

    US20130177784A1

  • Method and device for manufacturing battery electrode

    JP2013084383A